Effects of T6 age hardening on microstructure and mechanical properties of Al-Si-Cu cast aluminium alloy - Amporn Wiengmoon (2018)
Effects of T6 artificial aging heat treatment on microstructure, microhardness and ultimate tensile strength of Al-4.93 wt% Si-3.47 wt% Cu alloy were investigated. The T6 age hardening treatment consists of solution treatment at 500±5°C for 8 hours followed by quenching into hot water at 80°C and artificial aging at 150, 170, 200 and 230°C for 1-48 hours followed by quenching into hot water. Microstructure was characterized by optical microscopy (OM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and transmission electron microscopy (TEM). XRD and SEM revealed that the microstructure in the as-cast condition consists of primary dendritic α-Al, acicular-plate and globular forms of eutectic Si and intermetallic phases including globular Al 2 Cu and a flake-shape Al 5 FeSi. By T6 aging hardening, some intermetallics were dissolved and spheroidized. The volume fraction of eutectic phases in the as-cast, solution-treated, and solution-treated plus aging at 170°C for 24 hours is 17%, 12% and 10%, respectively. TEM results showed that precipitates in under-aging condition at 170° C for 6 hours are in the form of disc shape with the diameter in the range of 7-20 nm. At peak aging at 170°C for 24 hours, thin plate precipitates with about 3-10 nm in thickness and 20-100 nm in length were found, lengthening to about 30-200 nm at longer aging time. The microhardness and ultimate tensile strength were increased from 71 HV0.05 and 227 MPa in the as-cast condition up to 140 HV0.05 and 400 MPa after solution treatment plus aging at 170°C for 24 hours, and decreased at prolong aging time. © (2013) Trans Tech Publications, Switzerland.